2021
DOI: 10.5489/cuaj.7265
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radiotherapy for localized prostate cancer on bladder function as demonstrated on urodynamics study: A systematic review

Abstract: Introduction: This study aimed to describe the effects of bladder function following radiotherapy for localized prostate cancer by performing a systematic review on studies reporting on urodynamic findings after radiotherapy. Methods: This systematic review was conducted in accordance with PRISMA guidelines. The review protocol was registered at PROSPERO (CRD42021229037). A systematic search was conducted using PubMed, Cochrane Library, Scopus, and OVID Embase. Studies were included if they involved men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…In particular, storage symptoms might be more affected by pelvic RT than voiding symptoms, which was indicated by the significant deterioration of OABSS and VV, although no significant changes were observed in individual items of IPSS regarding storage symptoms, probably due to the small size of the cohort. One possible explanation is that RT reduces bladder compliance over time due to fibrosis of the detrusor and impairment of blood flow, 20 which results in the longitudinal deterioration of storage functions and symptoms. Nevertheless, RT should not be considered as a contraindication of AUS implantation, because significant improvements of UI and QOL could not be obtained without AUS in patients with severe UI.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, storage symptoms might be more affected by pelvic RT than voiding symptoms, which was indicated by the significant deterioration of OABSS and VV, although no significant changes were observed in individual items of IPSS regarding storage symptoms, probably due to the small size of the cohort. One possible explanation is that RT reduces bladder compliance over time due to fibrosis of the detrusor and impairment of blood flow, 20 which results in the longitudinal deterioration of storage functions and symptoms. Nevertheless, RT should not be considered as a contraindication of AUS implantation, because significant improvements of UI and QOL could not be obtained without AUS in patients with severe UI.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic literature reviews and metanalyses (SLRs) conducted according to the PRISMA guidelines (including an evidence-based minimum set of items for reporting) ( , accessed on 8 May 2021) are increasingly important in health care, keeping medical doctors up to date, and also representing the background for developing clinical guidelines/trials, as well as the justification for financial supports of research projects. Usually conducted by multidisciplinary teams, SLRs performed according to these guidelines could be applicable in various topics/contexts, improving the research quality not only of pure meta-analyses but also of SLRs applied to case report/series [ 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , …”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps a result of the discrepancy in the mean age of KT (44) and pelvic interventions that can lead to BOO such as radical prostatectomy, anti-incontinence surgeries, and pelvic radiation for various malignancies, which typically occur in the 5th to 7th decades of life [42][43][44][45]. In non-KT patients, a systematic review of post-radiotherapy prostate cancer patients by Yao et al in 2021 found significantly reduced bladder capacities compared to non-radiated patients, as well as impaired bladder compliance in 18.8-62.5% and de novo DO in 13.3% of patients [46]. The significance of these UDS findings on outcomes or management is unknown.…”
Section: Prior Urologic or Pelvic Interventionsmentioning
confidence: 99%